Utilization of AR Technology for The Development of Speech Therapy Applications by Optimizing Marked-Based Tracking Method - Wanti, Linda Perdana; Somantri, Oman; Karyati, Titin (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2023)
Autism is a developmental disorder that attacks children mentally and causes difficulties in interacting with the social environment. Therapy that can be done to people with autism to deal with communication disorders is speech therapy. Application usage health or better known as mobile health is easy and fast to help users in accessing information about various health problems, one of which is child development or better known as an autism spectrum disorder (ASD) which was developed using augmented reality (AR) technology. The purpose of the study is to optimizing the marked-based tracking method to augmented reality technology for speech therapy tutorials for children with autism. The results obtained from this study are the SELPY application (Self Autism Therapy) mobile-based speech therapy for people with autism which is a product of the application of appropriate technology in the field of information technology, especially in the health sector. The marked-based tracking method has been successfully implemented in the development of speech therapy AR applications for children with autism spectrum disorder (ASD). This is by the results of the tests that have been carried out, namely distance testing and angle testing. The most ideal distance to detect marker/image targets is 40cm to 50cm with a smartphone tilt angle of 200 to 300.